Philip Morris toxicological experiments with fresh sidestream smoke: more toxic than mainstream smoke - Schick, S (BMJ Group, 2005)
Background: Exposure to secondhand smoke causes lung cancer; however, there are little data in the open literature on the in vivo toxicology of fresh sidestream cigarette smoke to guide the debate about smoke-free workplaces and public places. Objective: To investigate the unpublished in vivo research on sidestream cigarette smoke done by Philip Morris Tobacco Company during the 1980s at its Institut für Biologische Forschung (INBIFO). Methods: Analysis of internal tobacco industry documents now available at the University of California San Francisco Legacy Tobacco Documents Library and other websites. Results: Inhaled fresh sidestream cigarette smoke is approximately four times more toxic per gram total particulate matter (TPM) than mainstream cigarette smoke. Sidestream condensate is approximately three times more toxic per gram and two to six times more tumourigenic per gram than mainstream condensate by dermal application. The gas/vapour phase of sidestream smoke is responsible for most of the sensory irritation and respiratory tract epithelium damage. Fresh sidestream smoke inhibits normal weight gain in developing animals. In a 21day exposure, fresh sidestream smoke can cause damage to the respiratory epithelium at concentrations of 2 µg/l TPM. Damage to the respiratory epithelium increases with longer exposures. The toxicity of whole sidestream smoke is higher than the sum of the toxicities of its major constituents. Conclusion: Fresh sidestream smoke at concentrations commonly encountered indoors is well above a 2 µg/m(3) reference concentration (the level at which acute effects are unlikely to occur), calculated from the results of the INBIFO studies, that defines acute toxicity to humans. Smoke-free public places and workplaces are the only practical way to protect the public health from the toxins in sidestream smoke.